(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was conducted in an attempt to control chickpea(Cicer arietinum L.) wilt, caused by Fusarium oxysporum f. sp. ciceris,using antagonistic properties of soil microorganisms. It also aimed atavoiding problems resulting from the use of chemical fungicides. ATrichoderma sp. was isolated from the rhizosphere of a resistant chickpeavariety (ICCV-2) and a Bacillus sp. from the rhizosphere and rhizoplaneof the same variety. Both microorganisms proved to be effective incontrolling the disease. In addition, Trichoderma harzianum, which wasobtained from Giza Research Station in Egypt, was also antagonistic toFusarium oxysporum f. sp. ciceris Wilt incidence was significantlyreduced when chickpea was grown in pots containing soil mixed with anyof the three antagonists or when chickpea seeds were initially treated withthe seed-dressing fungicide Vincit at 2 ml/kg seeds. Trichodermaharzianum proved to be the best bioagent as it gave the lowest diseaseincidence. In the field, the two Trichoderma spp. were as effective asVincit in causing reduction in the wilt incidence. At the higherconcentration of 140 g/m 2 , the two antagonists were effective throughoutthe growth period, but they were less effective at the lower concentrationof 70 g/m 2 particularly at the seedling stage.